Redistribution and sustainability : competing imperatives in the South African hake fishery - Heistein, Pierre (School of Economics, 2015)
This paper focuses on the hake fishery and investigates to what extent the fishery has been transformed. It then discusses the institutional structure and incentive schemes in the fishery and evaluates the economic, social, and environmental impacts of quota redistribution.